2012
DOI: 10.35197/rx.08.03.e1.2012.10.bg
|View full text |Cite
|
Sign up to set email alerts
|

Aislamiento de bacterias promotoras del crecimiento de la rizósfera de plantas de guayaba (Psidium guajava)

Abstract: La producción de guayaba para el 2008 en el estado de Guanajuato fue de 177 Ha de superficie sembrada e igual número de superficie cosechada, producción en 1,130.80 Ton. En las prácticas agrícolas tradicionales se ha hecho un uso excesivo de fertilizantes minerales, los que, si bien es cierto, garantizan una buena producción son costosos y llegan a causar desequilibrios en los agroecosistemas por la contaminación del suelo, agua, y de los alimentos. En este trabajo se evaluó el efecto de cepas de Bacillus subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…The chemical and microbiological characterization of an organic fertilizer, based on the use of residues from the harvest of bananas, showed that the greatest presence of microorganisms found were bacteria, although the genus was not identified [20]. The finding in this research is very important, due to the role of bacteria of the genus Bacillus, associated with the promotion of plant growth and control of pathogens [21][22][23][24][25]. A relevant aspect that distinguishes the bacteria of this genus is the ability to produce endospores, as a resistance mechanism to various types of stress [24,26,27].…”
Section: Resultsmentioning
confidence: 99%
“…The chemical and microbiological characterization of an organic fertilizer, based on the use of residues from the harvest of bananas, showed that the greatest presence of microorganisms found were bacteria, although the genus was not identified [20]. The finding in this research is very important, due to the role of bacteria of the genus Bacillus, associated with the promotion of plant growth and control of pathogens [21][22][23][24][25]. A relevant aspect that distinguishes the bacteria of this genus is the ability to produce endospores, as a resistance mechanism to various types of stress [24,26,27].…”
Section: Resultsmentioning
confidence: 99%
“…A partir de la aplicación del tratamiento se tomaron mediciones diarias del largo del tallo y número de foliolos por 60 días. En el día 60 se evaluaron: largo de raíz, peso húmedo de plántulas, peso húmedo de raíz, peso seco de plántula, peso seco de raíz, peso húmedo de tallo y hojas, porcentaje de humedad de plántulas y porcentaje de humedad de raíz (Gómez-Luna et al, 2012;Mena-Violante et al, 2009;Airola, 2010). El experimento fue realizado bajo un diseño ANOVA completamente al azar con un nivel de significancia de 0.05 y comparación de medias de Tukey.…”
Section: Assessment Of Seed's Growth Promotionunclassified
“…After the treatments, we took daily measurements along the stem and the number of leaflets on those 60 days. On day 60, we assessed root length, seedling wet weight, root wet weight, seedling dry weight, stem and leaves wet weight, seedling moisture percentage and root moisture percentage(Gómez-Luna et al, 2012;Mena-Violante et al, 2009;Airola, 2010). The experiment used a fully randomized ANOVA design, with a significance level of 0.05 and Tukey's mean comparison test.The three strains of B. subtilis were capable of producing siderophores, as demonstrated by the halos in CAS media(Figure 1).…”
mentioning
confidence: 99%
“…Despite notable progress, there remains a lack of knowledge regarding the impact of PGPR on tropical tree species, including Schizolobium parahyba (Gómez-Luna et al, 2012).…”
Section: Introductionmentioning
confidence: 99%